KUALITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN DITINJAU DARI INDEKS KEPUASAN MASYARAKAT DI KECAMATAN TANJUNGPINANG KOTA KOTA TANJUNGPINANG PROVINSI KEPULAUAN RIAU - Marthalina marthalina88@gmail.com; Muhammad Fadil (Institut Pemerintahan Dalam Negeri, 2017)
The government has the obligation and responsibility as a provider of public services to meet the needs of the community, which is implemented by both central government agencies, in regional and State-Owned Enterprises. Services that can be provided in the form of goods or merit services. Services provided by the government to the public must be qualified. For that there is a community satisfaction index that is intended for government agencies services units where the results can be used as a reference for the agency service providers to improve and enhance the quality of services provided to the community. A quality service can make people become satisfied. The purpose of this research to determine the District Integrated Administrative Service Quality in terms of Community Satisfaction Index in the District of Tanjungpinang City Tanjungpinang City of Riau Islands province. The research design used is descriptive qualitative research with an inductive approach. The technique of collecting data through interviews, observation, documentation and triangulation. Data were analyzed using data reduction, data tabulation and conclusion. Research results obtained that the quality of the integrated administrative service districts in the District of the City Tanjungpinang already qualified, it is known after a review of the results of community satisfaction index where the value obtained is 75.575 which can be practically considered good or quality. Keywords: quality, service, government